Weather changes influence the crime activity towards the quality of life / Anis Zulaikha Mohd Zukri, Siti Rasidah Md Sakip and Suraya Masrom - Mohd Zukri, Anis Zulaikha; Md Sakip, Siti Rasidah; Masrom, Suraya (Universiti Teknologi MARA, Perak, 2023)
The controversy over weather changes will lead to more stress, less social control, reduced social support, criminal tendencies, more possibilities for crime, and societal conflict. The factors driving criminal activity have received much attention, and voluminous literature has related the incidence of changing weather changes to criminal activity. However, weather variables can affect the environment and human behaviour differently. For example, past scholars found that homicidal crime has a connection with the weather change. However, although studies look at the relationship between crime and weather change, the source of the data is debatable. In addition, empirical studies showing the relationship between property crime and weather change are challenging to obtain because none can be found. Therefore, this paper aims to identify the pattern of criminal activity based on weather changes to address this situation. In this paper, the research methodology uses quantitative data. The crime data were gathered from the Royal Malaysia Police (RMP), and the weather data was gathered from Meteorological Department for Selangor, Kuala Lumpur, and Johor from 2011 to 2020. The data were analysed using SPSS statistical and illustrated in the bar graph method to identify the pattern and relationship between crime and weather. This study found that non-aggressive and property crime is less influenced by the high temperature but influenced by the ambient temperature and humidity. Future research on the relationship between crime and weather towards the quality of life of people must be theoretically grounded and use measures of crime and weather that are justified by the quality-of-life index theory.